Adaptation constraints and prospects for future research priorities in lowland rice-based farming systems: learning experiences from Northwest Cambodia - Van Touch; Rebecca Cross; Clemens Grünbühel; Floris Van Ogtrop; Peter Ampt; Try Yorn; Robert John Martin; Brian R. Cook; Daniel K. Y. Tan (Environment, Development and Sustainability, 2023)
Sustainable agricultural development not only addresses global food insecurity but may also alleviate poverty by enriching the lives of millions of smallholder farmers. Improving the sustainability and profitability of agriculture where smallholders are dominant creates profound impacts because small landholding farmers produce approximately 70–80% of the global food. The need for a thorough understanding of the factors affecting farmers’ adoption of agricultural technologies and practices has been identified from extant literature as an important research gap. Responding to the research gap and need, this study examined the challenges that prevent farm households from adopting improved farming practices and/or technologies in Banteay Meanchey and Battambang provinces in Northwest Cambodia. A total of 524 rice producing farm household representatives were randomly selected from a household database maintained by the local government authorities. A mixed methods approach was used in the study including semi-structured interviews followed by in-depth interviews, field observations, and literature review. Farmers were found to be confronted with a range of challenges and concerns, including soil degradation, weeds, diseases, insect pests, high production costs, flooding, droughts, changing rainfall pattern, and unreliable rainfall distribution. The research findings demonstrate that improved crop production practices (e.g., adopting mechanised direct seeding methods of crop establishment, maintaining and improving soil health through crop residue retention, growing cover crops, etc.) and better resource use efficiency (e.g., reducing seeding rates to less than 100 kg/ha, being more strategic in the use of integrated nutrient, weed, and pest management strategies, etc.) can be a starting point for sustainable intensification of rice production. This transition towards intensifying paddy production sustainably may become even more effective through a clear understanding of local contexts, farm household characteristics, available resources, and the farm management practices and constraints. We observed that farmers and their associations have yet to be fully recognised as partners and actors in Cambodia. Instead, they tend to be viewed as beneficiaries and recipients of improved practices and technologies. We, therefore, propose that farmers and their associations be acknowledged and included in a process of co-creation of knowledge-practices. Such partnerships will enable the inclusion of factors (e.g., production costs, production risks, complexity and practicability of implementations, product market and prices, etc.) shown to influence farmers’ adoption of innovative farming practices and technologies. The original contribution of this article is a real-world account of the constraints and limitations experienced by smallholder rice farmers in Cambodia, which are connected to future research and development priorities in the region.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)